Marketing Extension Of Marketing Area (Distribution Channel) In Ketumbar Crackers (Kriuk Baren) Business In Curah Lele Village, Balung District, Jember District - Robustin, Tri Palupi (IMPOWERMENT SOCIETY, 2020)
Distribution channels have an important role in the distribution of a product from producers to the end consumers in order to meet the wants and needs of consumers. This is one of the obstacles for UMKM in expanding distribution channels. Coriander Crackers (Baren’s Kriuk) is a small and medium business that was established around the end of 2018 which is located in the village of Curah Lele Balung District Jember Regency. The problem faced by the home industry of coriander crackers barri 's kriuk is in the field of marketing especially the marketing area (distribution channel) which is less expanded, especially in the jember city area. Community service activities are expected to produce targets in accordance with partner expectations, namely: (1) Broader marketing area (distribution channels) so that products are better known to the wider community; (2) Better packaging innovation.